Impact of Latest Technology in Mandalika MotoGP Tourism PR: SWOT Review - Awaloedin, Dipa Teruna; Pradini, Gagih; Bule, Yohana Gaius; Andini, Davi Ayu (CV ODIS, 2024)
This study explores the integration of digital technology in tourism promotion, focusing on the transformative impact of social media, AI, and big data. Using qualitative methods and SWOT analysis, the paper discusses the challenges and opportunities in Indonesian tourism, emphasising the recent success of Mandalika MotoGP's digital PR activities. The results highlight the role of AI and big data in revolutionising market research, sentiment analysis, and crisis management. Despite challenges like data security and digital literacy, strategies to optimise digital technology in tourism PR are outlined, including improving ICT infrastructure and creating engaging digital content.